Odpowiedzi

  • el21
  • Początkujący
2010-03-12T22:18:04+01:00
1)delta=1 ; x=1/6
2)3x²-9x+6≤0 ; delta=9 ; x1=9-3/6=1 , x2=9+3/6=2
3) (x⁴ +2x³ -6x²-4x) : ( x-2)=(x³+4x²+2x)*(x-2)
4) 12x-4y-6=12x-3y --> y=-6
x+y/2=4,5+y-1/3 --->x=11/6
2010-03-12T22:23:16+01:00
Zad.1

4x²-4/3x+1/9=0 a=4 b= -4/3 c=1/9
Δ=b²-4ac
Δ=(-4/3)²-4*4*1/9
Δ=16/9-16/9
Δ=0 x₀=-b/2a
=4/3/8=4/3 :8=4/3*1/8=4/24=1/6

zad.2
-4x+8≤-3x²+5x+2
-4x-5x=-3x²+2-8
-9x=-3x²-6
-3x²+9x-6=0 a=-3 b=9 c=-6
Δ=b²-4ac
Δ=81-72
Δ=9
Δ=3 x₁=-b-pierwiastek z delty przez 2a
= -9-3/-6
=-12/-6=2
x₂=-b+pierwiastek z delty przez 2a
x₂=-9+3/-6=-6/-6=1